Transformation of the highest political elite in Russia after Peter the Great in the process of “palace coups” - D. A. Filimonov (Вестник университета)
The article is devoted to the study of the transformation of the highest political elite of the Russian Empire after the death of Peter the Great. This is one of the most difficult and dramatic periods in Russian history, called the era of “palace coups”. The main properties of the Russian political elite formed by the reforms of Peter the Great are analyzed, its main features are determined that influenced the nature of the intra-elite struggle and led to the transformation of the highest political elite in Russia. The composition and goals of the main court groups that fought for power under Catherine I, Peter II, Anna Ioannovna are considered in detail. The formation of such bodies as the Supreme Privy Council under Catherine I and the Cabinet of Ministers under Anna Ioannovna and their influence on ensuring the interests and transformation of the highest political elite are analyzed. Attempts to limit royal power by members of the Supreme Privy Council were considered and conclusions were drawn about the reasons for their failure.